Diagnostic and Therapeutic Capability of Double-Balloon Enteroscopy in Clinical Practice - Umit Akyuz; Filiz Akyuz (Korean Society of Gastrointestinal Endoscopy, 2016)
Advances in technology have facilitated the common use of small-bowel imaging. Intraoperative enteroscopy was the gold standard method for small-bowel imaging. However, noninvasive capsule endoscopy and invasive balloon enteroscopy are currently the main endoscopic procedures that are routinely used for small-bowel pathologies, and the indications for both techniques are similar. Although obstruction is a contraindication for capsule endoscopy, it is not considered to be problematic for double-balloon enteroscopy. The most important advantage of double-balloon enteroscopy is the applicability of therapeutic interventions during the procedure; however, double-balloon enteroscopy has certain advantages as well as disadvantages.